2011
DOI: 10.2113/econgeo.106.3.359
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Gold Mineralization in an Orogenic Setting--The Bohaun Deposit, Western Irish Caledonides

Abstract: The Bohaun gold deposit in County Galway, western Ireland is located in the Caledonian orogenic belt, proximal to a major accretionary boundary. The mineralization is hosted in a normal extensional fault, representing a zone of repeated extension and vein infilling of open cavities, within clastic sedimentary rocks, which have only reached the late diagenetic zone of low-grade metamorphism.The mineralization consists of undeformed veins, stockworks and breccias. Quartz dominates all the veins and commonly disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 61 publications
(73 reference statements)
1
13
0
Order By: Relevance
“…Alongside deposit scale studies of other regionally important discoveries, such as Croagh Patrick (Aherne et al, 1992;Wilkinson and Johnston, 1996) and Cregganbaun (Thompson et al, 1992), all have indicated orogenic style mineralisation. However Lusty et al (2011) suggest a role for low temperature Cl-rich basinal brine-type fluids for the mineralisation at Bohaun (Co. Galway), similar to those invoked for the final phases of mineralisation at Curraghinalt (Parnell et al, 2000) and red-bed Au-Pd mineralisation.…”
Section: Gold Mineralisation In Irelandmentioning
confidence: 76%
See 2 more Smart Citations
“…Alongside deposit scale studies of other regionally important discoveries, such as Croagh Patrick (Aherne et al, 1992;Wilkinson and Johnston, 1996) and Cregganbaun (Thompson et al, 1992), all have indicated orogenic style mineralisation. However Lusty et al (2011) suggest a role for low temperature Cl-rich basinal brine-type fluids for the mineralisation at Bohaun (Co. Galway), similar to those invoked for the final phases of mineralisation at Curraghinalt (Parnell et al, 2000) and red-bed Au-Pd mineralisation.…”
Section: Gold Mineralisation In Irelandmentioning
confidence: 76%
“…6) indicates a second source of Pb, more radiogenic in nature, was involved in the mineralisation together with source 2. The radiogenic Cregganbaun end member has similar isotopic ratios to vein gold from Bahaun, Co. Galway (also the Mayo subterrane), and Lusty et al (2011) proposed an association with post-Caledonian (Carboniferous or later) Cl-rich basinal brine-type fluids, similar to those involved in red-bed Au-Pd mineralisation (see Chapman et al, 2009) and one of the four mineralisation phases at Curraghinalt (Parnell et al, 2000). However such gold typically contains very low Ag, has alloys in the Au-Pd-Hg system, and is characterised by an inclusion suite containing selenides and tellurides and absent of sulphides.…”
Section: Late Caledonian Nwt Mineralisation and Radiogenic Crustal Pbmentioning
confidence: 92%
See 1 more Smart Citation
“…Reactivation of D3 faults during these extensional events could have remobilised gold. This is supported by evidence from the distribution and character of alluvial gold in the Thornhill area (Leake and Cameron, 1996;Leake et al, 1998) and by atypical oxide-related lode-gold mineralisation in Western Ireland (Lusty et al, 2011). It is likely that regional hydrothermal activity and Pb-Zn-Cu-Ag vein mineralisation was related to this tectonic reactivation (Baron and Parnell, 2005;Wilkinson et al, 1999).…”
Section: Timing Of Deformationmentioning
confidence: 68%
“…δ 34 S values for sulphide minerals from a gold-bearing vein within the Fleet pluton near Talnotry (Orchars Vein; Figure 1) are between -12 and -5 ‰; comparable with those for Pb-Zn veins at Leadhills-Wanlockhead (Anderson et al, 1989), and therefore are considered to reflect low temperature meteoric remobilisation during a significantly later episode of structural reactivation (Anderson et al, 1989;Baron and Parnell, 2000;Lowry et al, 1997;Lusty et al, 2011;Samson and Banks, 1988).…”
Section: Sulphur Isotopesmentioning
confidence: 77%